(untitled) (Research, Society and Development, 2022)
To identify strategies for attracting pregnant adolescents to prenatal consultations. This is an integrative review of the literature and a qualitative approach, of a descriptive nature, a research method that consists of aggregating and synthesizing research results on a particular topic, in a methodical and structured way, with the health indexation bases being researched , Scientific Electronic Library Online (Scielo), PubMed, and Virtual Health Library (BVS), as this platform provides access to the databases of Latin American and Caribbean Literature on Health Sciences (LILACS). Through the search methods in relation to the articles selected for the present study, 18 articles were selected for the study, which promoted the detection of the objections faced by pregnant adolescents in adhering to prenatal care, implementing the nurse’s performance contributing to the early capture of these pregnant adolescents. The present study had as a limitation the difficulty in finding and selecting articles with content directed to the applied theme, however, it was observed that the objective of this study proved to be relevant for identifying the difficulties faced by pregnant adolescents in adhering to consultations of prenatal care, as well as the extreme importance of the nurse’s work process in the active search and early capture of pregnant adolescents for consultations.